Design and research of combined magnetron-ion-beam sputtering system - Dudin, S.; Tkachenko, O.; Shchybria, A.; Yakovin, S.; Zykov, A.; Yefymenko, N. (Вопросы атомной науки и техники, 2018)
The design and characteristics of a new combined magnetron-ion-beam sputtering system are presented. The system allows coating deposition both by means of magnetron discharge, and by sputtering of complex composite targets by high-energy ion beam. Computer simulation and optimization of magnetic field topology on the system, which is common for the magnetron discharge and the Hall-type ion source, have been carried out. The ignition curves, current-voltage characteristics of the system, in dependence on gas type and pressure, magnitude and topology of magnetic field have been researched both for autonomous operation of the planar magnetron discharge and ion source and for their combination. Spatial distributions of ion current are also presented.